Border Protection Task Force and Soft Power Defense Diplomacy in the Oecusse Border Dispute - Nahadin, Mallini Anthonia; Perwita, Anak Agung Banyu; Hendarwoto, Yermia (International Journal of Education, Culture, and Society, 2025)
This study addresses a notable gap in the literature concerning the intersection of defense diplomacy and post-colonial border governance, with a specific focus on Indonesia and Timor-Leste’s Oecusse enclave. Despite the region’s strategic relevance and humanitarian sensitivities, limited scholarly attention has been given to the soft power dimensions of military engagement in this context. The research aims to analyze how Indonesia’s Border Protection Task Force (Satgas Pamtas) operationalizes soft power-driven defense diplomacy to manage low-intensity border frictions and sustain stability in Oecusse. Utilizing a qualitative case study approach, data were collected through document analysis, policy reports, and expert interviews with thirty purposively selected respondents. Thematic and pattern-matching analysis was applied to identify recurring mechanisms of cooperation and confidence-building. Findings indicate that Indonesia’s defense diplomacy manifested through joint patrols, humanitarian outreach, and cross-border community engagement serves as a non-coercive strategy for conflict prevention and mutual trust enhancement. These practices underscore the evolving role of military institutions as diplomatic actors in regional security governance. The study affirms the theoretical link between soft power and border management, illustrating how defense initiatives can contribute to peacebuilding without escalating tensions. It concludes that institutionalizing localized confidence-building measures, promoting civilian involvement, and integrating traditional adat structures into formal bilateral mechanisms are crucial for achieving sustainable peace. The study further recommends future comparative research on border diplomacy across Southeast Asia to refine the hybrid defense diplomacy model presented.